Antibacterial Activity Test of Herbal Liquid Soap Against Streptoccus pyogenes and Candida albicans - Darini Kurniawati (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Nowadays people like to use liquid soap because it is more practical and easier to store. Antiseptic liquid soap circulating in the market uses chemical compounds such as triclosan, hexalorofen and bithional whose raw materials are from abroad. The government encourages the use of its own natural raw materials so that natural materials will become the mainstay of Indonesian industry. The purpose of this research was knowing the antibacterial effectiveness of herbal liquid soap against Streptococcus pyogenes and Candida albicans. This research used true experimental method which the process was started by making herbal liquid soap products using the hot; and cold press method for evaluating pH, organoleptic, foam stability, water content, free fatty acids and free alkali, testing germ numbers with the intervention group (washing hands with herbal liquid soap). and control group (washing hands with running water), followed by testing the inhibitory power of herbal liquid soap against Streptococcus pyogenes and Candida albican microbes. The results of the evaluation test of herbal liquid soap have a liquid form, lemon odor and yellow color, foam height 15-70 mm, pH 10, water content 52%, free fatty acids 0.05%, free alkali 0.091%, according to SNI soap standards. required liquid. Antibacterial test by dilution method and continued with microbial inhibition results obtained MIC against Streptococcus pyogenes at a concentration of 20% and MBC at a concentration of 20% of 22mm. Against Candida albican, the results of MIC at a concentration of 25% and MBC at a concentration of 25% were 15 mm.